2004
DOI: 10.1051/0004-6361:20040403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of solar coronal loops

Abstract: Abstract. This work addresses the problem of plasma condensation and "catastrophic cooling" in solar coronal loops. We have carried out numerical calculations of coronal loops and find several classes of time-dependent solutions (static, periodic, irregular), depending on the spatial distribution of a temporally constant energy deposition in the loop. Dynamic loops exhibit recurrent plasma condensations, accompanied by high-speed downflows and transient brightenings of transition region lines, in good agreemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
148
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 17 publications
23
148
1
Order By: Relevance
“…Bakhareva et al (1992) showed that plasma partial ionisation causes dynamic regimes to exist in a prominence, which extends the range of oscillation periods. Numerical studies of prominence condensations (Karpen et al 2001;Müller et al 2004) have revealed mass cyclic variations with time periods similar to our observations. As yet, no observational study was carried out to confirm their existence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Bakhareva et al (1992) showed that plasma partial ionisation causes dynamic regimes to exist in a prominence, which extends the range of oscillation periods. Numerical studies of prominence condensations (Karpen et al 2001;Müller et al 2004) have revealed mass cyclic variations with time periods similar to our observations. As yet, no observational study was carried out to confirm their existence.…”
Section: Discussionsupporting
confidence: 87%
“…The periods obtained by Karpen et al (2001) were 22 h and 15.3 h for loops of length 340 Mm and 180 Mm respectively. Müller et al (2004) found periods near 11 h for a loop of length 100 Mm. The possible interpretation of our observations suggests that the spatial and time evolution of emission above and surrounding the EUV filament reflects the evolution of the corona and condensation masses.…”
Section: Discussionmentioning
confidence: 96%
“…In this late phase the dominant heating of the apex is due to heat conduction from the sides. Potentially, such situations can lead to a loss of equilibrium and catastrophic cooling (Müller et al 2003(Müller et al , 2004), which we do not observe here because the heating is not concentrated strongly enough towards the footpoints. In 3D models with a more stable magnetic field configuration, the loop can reach a (quasi-)equilibrium state, and remain stable for a longer time (Peter & Bingert 2012).…”
Section: Cooling Phasementioning
confidence: 74%
“…By using the width of the line in Hα as a proxy, Antolin and Rouppe van der Voort (2012) give upper limits for Hα coronal rain centered around 7000 K but with a long tail to higher temperatures up to 5 × 10 4 K. It has not been possible to measure densities directly so far, but estimates are made based on numerical simulations of the phenomenon (Müller, Hansteen, and Peter 2003;Müller, Peter, and Hansteen 2004;Tsiklauri et al 2004;Mendoza-Briceño, Sigalotti, and Erdélyi 2005;Mok et al 2008;Antolin, Shibata, and Vissers 1 Most of these observations are done with imaging instruments and thus the speeds correspond to projected values in the plane of the sky. However, since all reports correspond to off-limb observations, the values are close to the total velocities, as confirmed by the spectropolarimetric observations in Antolin and Rouppe van der Voort (2012). 2010; Murawski, Zaqarashvili, and Nakariakov 2011).…”
mentioning
confidence: 99%